The effect of quercetin on endothelial cells is modified by heterocellular interactions. Issue 5 (4th May 2020) - Tumova, Sarka; Houghton, Michael J.; Williamson, Gary
Abstract : Single cell-type models are useful for determining mechanisms, but in vivo, cell–cell interactions are important, and neighbouring cells can impact endothelial cell function. Abstract : Single cell-type models are useful for determining mechanisms, but in vivo, cell–cell interactions are important, and neighbouring cells can impact endothelial cell function. Quercetin can attenuate endothelial dysfunction by modulating vascular tone and reducing inflammation. We determined the effect of quercetin on a co-culture between Human Umbilical Vein Endothelial Cells (HUVEC) and human HepG2 hepatic cells or human LHCN-M2 muscle cells. Heme oxygenase-1 (HO-1) mRNA and protein were decreased, pyruvate dehydrogenase kinase (PDK) 4 and glucose transporter (GLUT) 3 mRNA increased, and GLUT1 protein decreased in HUVEC when cultured with HepG2. GLUT transporters, but not the other targets, were similarly regulated in co-culture with muscle cells. Some but not all of the effects were mediated by lactate and transforming growth factor β1. Quercetin added apically to the endothelial cells upregulated HO-1 and downregulated PDK4 both in monoculture and in co-culture, but the total PDK4 levels were higher in the presence of HepG2 cells. In the absence of general permeability changes, glucose transport across the endothelial monolayer was elevated in the presence of HepG2 cells, however this effect was moderated by quercetin applied on the apical side of the endothelial cells. At lower glucose concentration, apical quercetin also promoted glucose uptake in HepG2 cells. Co-culturing HUVEC with the HepG2 cells showed capacity to modulate quercetin-elicited changes in endothelial gene transcription and glucose transport.